KNOWLEDGE AND AWARENESS REGARDING BIOMEDICAL WASTE MANAGEMENT AMONG EMPLOYEES OF A TERTIARY CARE HOSPITAL - Bansal, Manoj; Mishra, Ashok; Gautam, Praveen; Changulani, Richa; Srivastava, Dhiraj Kumar; Gaur, Neeraj Singh (Indian Journal of Community Health, 2013)
Background: A hospital is an establishment where the persons suffering with the variety of communicable and non communicable diseases are visiting to take medical care facilities. Hospitals and other healthcare establishments in India produce a significant quantity of waste, posing serious problems for its disposal, an issue that has received scant attention. Objective: To assess the level of knowledge regarding biomedical waste and its management among hospital personnel. Material and Methods: The present study was a cross sectional study carried out in a tertiary care hospital of Gwalior in year 2008. Medical, para-medical and non-medical personnel working at their current position for at least 6 months were included as study participants. Self made scoring system was used to categorize the participants as having Good, Average and Poor knowledge. Statistical Analysis: Percentage and Proportion were applied to interpret the result. Results: The score was highest for medical and least for non-medical staff. Conclusion: The present study concludes that regular training programs should be organized about the guidelines and rules of biomedical waste management at all level.